Strategi Pemasaran Gerai Area Tugu Malioboro Di Bandar Udara Internasional Yogyakarta - Dandi Yudisthira; Nanik Riananditasari (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract. This research took place at Angkasa Pura I Yogyakarta International Airport (YIA) branch. This study aims to find out how the strategy carried out by the Tugu Malioboro Yogyakarta international airport branch uses the SWOT analysis method. SWOT analysis is a form that is used by the management of a systematic company organization and can assist in the company's efforts to develop a mature plan to achieve the goals of the company or organization. The type of research used in this research is qualitative research. Sources of data in this study used secondary data and primary data, namely data sources obtained by reading, studying and understanding through other media sourced from literature, as well as company documents and by conducting interviews with the Director of KTM, commercial managers and with the heads of outlets at Tugu. malioboro. The results of the discussion of this thesis show that the results of the SWOT analysis assessment state that external factors are stronger than internal factors, which means that the Tugu Malioboro branch of the Yogyakarta international airport cannot only rely on the strengths they have because besides these strengths there are also strong weaknesses. Therefore, the management of the Malioboro Monument area at the Yogyakarta international airport must be able to take advantage of the strengths and opportunities that exist, and be able to minimize weaknesses and be able to avoid threats by using some of the resulting strategies.